ナンキョクイキ ノ エイセイ カンソク - 瀬古, 勝基; セコ, カツモト; Seko, Katsumoto (1997)
P(論文) ACR期間中に昭和基地で受信された, NOAA・AVHRRデータは, 東南極の約半分の領域を1kmの分解能でカバーしており, 南極域の様々な大気と雪氷の情報を抽出することができる。衛星は, 宇宙空間から下向きに現象を眺める道具であり, NOAA・AVHRRが観測できる可視から熱赤外域にかけての波長帯では, 大気の上部から下部にかけての現象, そして雪氷面の観測が可能である。南極域としては高頻度(約1日1回)で等質のデータが1年間連続して取得されたことを利用して, 以下の解析を試みた結果を示す。1) 熱赤外チャンネルの時系列変化, 2) カタバ風の情報の抽出, 3) 雪氷面の地形と堆積環境の抽出。 The NOAA Satellite AVHRR data received at Syowa Station offer simultaneous images on 5 wavelengths covering an area 2000km on a side with resolution of 1km, and are useful for helping to clarify a number of phenomena. The AVHRR is a radiometer which observes in 4 or 5 channels covering the visible and infrared regions. Phenomena in the atmosphere and at the snow surface can be studied from the AVHRR data. Data are received from at least one orbit per day and are of uniform quality. The following analysis are carried out. Results of the following analyses are summarized in this report. 1) Analysis using the time sequence of infrared channel data, 2) Detection of the katabatic wind information, 3) Detection of the ice sheet surface and snow accumulation information. departmental bulletin paper